Sensing Hinduism: Lucian-Indian Funeral Feast as Glocalized Ritual1 - Manian, Sabita (Religions, 2016)
Migrant narratives of Indo-Caribbean religious practices in the smaller island states of the Caribbean are rare, and that Diaspora's funerary traditions are even less explored. This scholarly lacuna is addressed here by using data from ethnographic research conducted in St. Lucia to examine the funerary ritual of a Lucian-Indian feast through the multidisciplinary lens of glocalization. Specifically, we investigate the following: (a) ways that the diasporic identity of Lucian-Indians has been adapted and re-configured within a local-global nexus; (b) the extent to which there has been a local construction of a distinct socio-spatial identity among Lucian-Indians, one retaining Hinduness even as they assimilated into the larger St. Lucian society; and (c) whether glocal characteristics can be identified in the performance of a particular funeral feast. Following Roudometof, we posit that many aspects of a Lucian-Indian ethno-religious funerary ritual demonstrate indigenized and transnational glocalization.